An Experimental and Comparative Performance Evaluation of a Hybrid Photovoltaic-Thermoelectric System - Khan, Muhammad Ahsan Iqbal; Khan, Muhammad Irfan; Kazim, Ali Hussain; Shabir, Aqsa; Riaz, Fahid; Mustafa, Nauman; Javed, Hassan; Raza, Ali; Hussain, Mohsin; Salman, Chaudhary Awais (Frontiers in Energy Research, 2021)
The majority of incident solar irradiance on the photovoltaic (PV) cells induces thermalization, which reduces their performance. Effective thermal management can be utilized to generate additional electrical power while simultaneously improving photovoltaic performance. In this work, an experimental model of a hybrid photovoltaic-thermoelectric generation (PV-TEG) system is developed in which 10 bismuth telluride based thermoelectric modules are attached to the rear side of a 10 watts polycrystalline silicon based photovoltaic module in order to recover and transform waste thermal energy to usable electrical energy. The experiment was then carried out for 10 days in Lahore, Pakistan, on both a simple PV module and a hybrid PV-TEG system. The findings revealed that a hybrid system can boost PV module output power and efficiency. The operating temperature of the PV module in the hybrid system is reduced by 5.5%. Due to a drop in temperature and the addition of some recovered energy by thermoelectric modules, total output power and conversion efficiency of the system increased by 19% and 17%, respectively. The results of this research could provide consideration of designing commercial hybrid PV-TEG systems.